Pengaruh Motivasi Dan Prestasi Praktik Kerja Industri Terhadap Minat Berwirausaha Pada Siswa Kelas XI Jurusan Akuntansi Di Smk Negeri 1 Karanganyar Tahun Ajaran 2015/2016 - Haris Kurniawan, Abdul, Dr. Wafrotur Rohmah, MM (2016)
The purpose of this study was to determine: 1) the effect of motivation on interest in entrepreneurship, 2) the effect of achievement working practices to the industry interest in entrepreneurship, 3) the influence motivation and achievement of working practices to the industry interest in entrepreneurship. This research is a quantitative descriptive research whose conclusions obtained based on the results of statistical analysis. The population in this study were all students of class XI Accounting Department SMK Negeri 1 Karanganyar 2015/2016 school year as many as 108 students with a sample of 84 students using simple random sampling technique. Methods of data collection using documentation and questionnaires. Questionnaire first be tested to determine the level of validity and reliability. Test requirements analysis in the form of normality and linearity test, to engineering data analysis using multiple linear regression analysis, t test, F test, the coefficient of determination as well as the effective contribution and relative contribution. Results of regression analysis regression equation: Y = 16.158 + 0.245 X1 + 2.312 X2 + e, which means that interest in entrepreneurship is affected by motivation and achievement of industry work practices. Based on the analysis and discussion can be concluded that: (1) motivation positive influence on interest in entrepreneurship. It is evident from the regression analysis obtained by value t count > t table is 4.145 > 1.989 with 0.000 significance value < 0.05. (2) the achievement of industrial work practices positive effect on interest in entrepreneurship. It is evident from the regression analysis obtained by value t count > t table is 2,725 > 1,989 with significant value 0.008 < 0.05. (3) motivation and achievement of industry work practices together positive effect on interest in entrepreneurship. It is evident from the regression analysis obtained F count > F table that is 14.786 > 3.11 with significant value 0.000 < 0.05. (4) motivational variables contribute effectively amounted to 17.9%. Variable achievement of industrial work practices contribute effectively amounted to 8.8%, with a coefficient of determination (R2) of 0.267, or 26.7%, while 73.3% are influenced by other variables not examined.